Phosphine- and pyridine-functionalized N-heterocyclic carbene methyl and allyl complexes of palladium. Unexpected regiospecificity of the protonation reaction of the dimethyl complexes - Danopoulos, Andreas A.; Tsoureas, Nikolaos; Macgregor, Stuart A.; Smith, Christopher (Organometallics, 2007)
Square planar neutral dimethyl and cationic allyl complexes of palladium with the electronically nonsymmetric diphenylphosphinomethyl- and pyridyl-N-heterocyclic carbene ligands have been synthesized and characterized. The products from the protonation of the dimethyl complexes with 1 equiv of acid at low temperatures are monomethyl cations, the exact nature of which is dependent on the type of ligand; in pyridine-carbene complexes the Pd-Me bond cleaved is trans to the carbene, while for the phosphino-carbene complexes it is trans to the phosphine. Density functional calculations suggest that protonation in these complexes occurs directly at the methyl ligands and that the site of protonation determines the selectivity of Pd-Me cleavage. For the pyridine-carbene complexes there is a clear preference for protonation trans to the carbene. For phosphino-carbene complexes, however, the site of protonation depends on the steric bulk of the N-heterocyclic carbene ligand. Protonation trans to carbene is favored with small substituents (H, Me), but the bulky 2,6-Pri2C6H3 susbstituent induces protonation trans to the phosphine, as is seen experimentally. © 2007 American Chemical Society.